EXPLORING THE INTERPRETATION OF BALIK MODAL AS â€œTHE OTHERâ€ BREAK EVEN POINT: A HERMENEUTIC ROMANTICS STUDY - Putra, Dimas Ramadhan; Kamayanti, Ari (Jurnal Ilmiah Mahasiswa FEB, 2013)
The accounting nowadays supports the capitalism. In this view, profit has been the cause of capitalism. Capitalism encourages private business to gain profit. However, there is ‘other’ accounting practice that does not seem to always end up in achieving profit as the main goal. This research is to explore the interpretation of balik modal as the other meaning of Break Even Point (BEP) using hermeneutics romantics approach. The result of this research is that there are different interpretations of balik modal as well as the underlying values. The first informant interpret that his balik modal is kulak equals to dapet where kulak is the money that he spends for raw and supplementary materials and dapet is his income or his selling. The other informant concept is Kulak = Dapet + Setoran. This is the comparison between Cak To, Mas Ambon, and the conventional BEP from the research that has been conducted before. Keywords: Bakso, Break Even Point, Balik Modal, Hermeneutic Romantics